The anti-diabetic potential of the African Adansonia Digitata L. plant extract - Badawy, Marwa Tawfik (AUC Knowledge Fountain, 2020)
Diabetes Mellitus (DM) is a severe chronic disease affecting a large population worldwide. The Middle Eastern region has been gifted with lots of native medicinal plants. However, there is less information on development of these medicinal plants into nutraceuticals for modulating specific diseases such as diabetes of common occurrence regionally. Towards this end, there is a crucial need to investigate other types of treatments to modulate diabetes. This study is conducted to fill in this gap by investigating medicinal plant used as folk medicine, which is Baobab (Adansonia digitata L.). This study is performed in two phases: in-vitro and in-vivo. The in-vitro part included extraction, assessment, and characterization of the baobab fruit pulp crude extract. The cytotoxic activity was assessed using MTT assay on L-929 fibroblast cells, with an IC50 value of 105.7 µg/mL, whereas DPPH was used to assess the antioxidant activity with calculated IC50 at 114.8 µg/mL. To characterize metabolites mediating for these effects, ultrahigh performance (UHPLC) analysis coupled to MS revealed for a total of 77 metabolites belonging to different chemical classes including organic acids, sugars, alcohols, phenolics, coumarins, and fatty acids. Almost 50% of the identified metabolites are reported for the first time in A. digitata fruits. In the second phase, the extract was tested in-vivo in an experimental streptozotocin (STZ) induced Sprague Dawley male rat model of diabetes. A. digitata L. low dose (150 mg/kg) injected i.p. twice a week showed potential hypoglycemic activity as revealed from several biochemical parameters such as fasting blood glucose, alkaline phosphatase, and blood urea nitrogen levels in comparison to high dose (300 mg/kg). Overall, the current study proves that Adansonia digitata L. has good potential as an antidiabetic, hepatoprotective, and reno-protective drug with a good safety margin.